2023
DOI: 10.1136/bmjgh-2023-012374
|View full text |Cite
|
Sign up to set email alerts
|

Levels and determinants of overprescribing of antibiotics in the public and private primary care sectors in South Africa

Mylene Lagarde,
Duane Blaauw

Abstract: Although overprovision of antibiotics in primary care is a key driver of antibiotic resistance, little is known about its determinants in low-income and middle-income countries. Patient demand and financial incentives for providers are often held responsible for overprovision. Yet, inadequate provision exists in their absence and could be fuelled by quality of care issues and incorrect beliefs of providers regarding patients’ expectations. We explored these issues in the private and public sector in South Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Clearly, inappropriate antibiotic prescribing is a complex process which is driven by several factors including lack of antibiotic prescribing guidelines, absence of antimicrobial stewardship programmes and inadequate knowledge of appropriate antibiotic prescribing (19,20). In addition, a major factor driving inappropriate antibiotic prescribing, is an effort by the physicians to use antibiotics to prevent infections i. e. prophylaxis (21).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, inappropriate antibiotic prescribing is a complex process which is driven by several factors including lack of antibiotic prescribing guidelines, absence of antimicrobial stewardship programmes and inadequate knowledge of appropriate antibiotic prescribing (19,20). In addition, a major factor driving inappropriate antibiotic prescribing, is an effort by the physicians to use antibiotics to prevent infections i. e. prophylaxis (21).…”
Section: Resultsmentioning
confidence: 99%
“…30 Studies have shown that inadequate antimicrobial treatment is an important risk factor for death in critical patients, suggesting that the aim should be to reduce the occurrence of this important problem by using efficient prophylactic methods. 31 Important studies have revealed the association of dysbiosis with the development of various pathologies including cardiovascular diseases, as the microbiota affects the host's immunity. 32 Because of the steadily increasing incidence of nosocomial infections related to cardiac surgery in the last decades, prophylaxis should mainly target the prevention and appropriate treatment of bacteremia associated with invasive hospital-based procedures performed in high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare professionals (HCPs) contribution in addressing antibiotic resistance plays a vital role. In order to to achieve this, focus must be on several key actions like: reducing inappropriate antibiotic prescription and distribution, reducing the sell of antibiotics at the over the counter (OTC) drugs without prescriptions, capacity building on AMR, monitoring the current usage and resistance patterns, and initiating antimicrobial stewardship (ASP) initiatives (Alam et al, 2023;Karimi et al, 2023;Lagarde & Blaauw, 2023). Along with three states that have already implemented the AMR Action Plan, India should urge other states to implement State Action Plan with newer initiatives that are appropriate to track and regulate the use of antibiotics, adhere to national action plan, and also focus on community and hospital-based research on public health aspects of AMR are all critically needed (Ahmed et al, 2019;Gelband & Delahoy, 2014;Sahni et al, 2020); (Ruckert et al, 2020).…”
Section: Discussionmentioning
confidence: 99%